Analysis of The Influence of Training and Capacity Development Programs on Improving Service Quality and Performance of Medical Personnel in Handling Patients - Yunus, Andri; Wilanda, Alifah; Hari Haji, Wachyu; Alatas, Abd. Rahman; Dharmawan, Donny (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
This work aims to address students' subjective perceptions of needs and problems in dealing with patient aggression. This research uses a cross-sectional study approach with a pretest-posttest design. Data was collected through interviews. From the results of the analysis, it was found that training in dealing with aggressive patients had a significant impact on improving the skills and self-confidence of nursing students. This training not only provides benefits on an individual level but can also improve overall results in the work environment. Integration of de-escalation topics into future training will be critical to increasing individual preparedness for situations that may occur in the workplace. Through a holistic and sustainable approach to developing education and training curricula in the health and nursing fields, students can be better prepared and confident in dealing with aggressive situations in nursing practice in the future.